'Better in kung fu movies than in political parties': Labour's Factionalism and a Reappraisal of Eric Hobsbawm's Political Thought. Issue 4 (21st October 2020) - Pike, Karl; Diamond, Patrick
Abstract: Eric Hobsbawm will forever be a giant intellectual figure. Yet, an aspect of his work is underappreciated—the case for a more pluralistic, dynamic and intellectually inquiring Labour Party. As such, his political thought is particularly relevant given the recent election of Keir Starmer, and the avowed quest for 'unity' in bringing Labour back to power. Hobsbawm came to believe that political strategies which sought to exploit social and political stratification and conflict—such as vilifying reformist political movements and those of moderate persuasion—doomed Labour to permanent opposition. A broad‐based people's party, uniting objectives of solidarity and aspiration, was the only viable class politics. Although from the Marxist tradition, Hobsbawm believed Labour's purpose was to make liberal democracy function more effectively, rather than creating an alternative economic and political system. Suggesting conflict was more suited to kung fu movies, Hobsbawm's predominant theme of 'anti‐factionalism with a purpose' remains apposite today.